Evaluasi Karakter Agronomis 15 Genotipe Hasil Persilangan Padi Gogo Lokal Bengkulu Pada Budidaya Organik Dan Anorganik Serta Ketenggangannya Terhadap Alumunium - Sri Mulatsih; Nurseha Nurseha (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2017)
Rice is one of strategic foods in Indonesia that can affect the inflation. Indonesian people and goverment have done many efforts to increase the national rice production, for example by extensification. However, it can not be said success because the rate of land transformation from rice field to other usages is much higher that the rate of extensification itself. Rice field transformation reaches 145.000 hectares each year. Due to that condition, growing rice in dry land (padi gogo) is a good alternative to improve national rice production. Longterm objective of this research is to create superior variety of dry land rice. The variety not only should be well adapted to Bengkulu Province climate and weather condition but also liked by local consumers. This research used split plot design as the use of ameliorant (farmyard manure and bokashi compost) as the main plot and 15 genotypes of dry land rice from cross breeding as the sub-plot. Result of research showed that there are 5 genotipe which tolelaran to poisoned of aluminium that is ( UNHZ 5, UNHZ 23, UNHZ 24, UNHZ 29 and UNHZ 31. The most highest production rice genotypes based on its lifespan are UNHZ 31